Hubungan Minat Baca Dan Ketersediaan Sumber Belajar Terhadap Prestasi Belajar Sejarah Di SMAN 2 Pariaman - Yoki Saputra; Hera Hastuti (Jurusan Sejarah FIS UNP, 2021)
Hubungan Minat Baca dan Ketersediaan Sumber Belajar terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS SMA Negeri 2 Pariaman Yoki Saputra1(*), Hera Hastuti2 1,2Jurusan Sejarah, Fakultas Ilmu Sosial, Universitas Negeri Padang *yokisaputra28@gmail.com Abstract This research departs from problems in learning history, especially the majority of students in class XII IPS at SMA Negeri 2 Pariaman have mid scores below the KKM (75). Then the observations were categorized into reading interest, the availability of learning resources and the low student achievement. This research is useful for analyzing the relationship between reading interest and history learning achievement of students in class XII social studies at SMA Negeri 2 Pariaman, the relationship between the availability of learning resources and the learning achievement of students in class XII social studies at SMA Negeri 2 Pariaman, the relationship between reading interest and the availability of learning resources to history learning achievement. Class XII IPS student at SMA N 2 Pariaman. This type of research is a quantitative study using the SPSS version 16 program. The population of this study were students of class XII IPS at SMA Negeri 2 Pariaman in the academic year 2020/2021 which consisted of 171 students, the sample of this study was 120 students who were randomly selected. The media feasibility test is carried out by validators who are proficient in their fields, namely history learning material experts. Data were collected using a questionnaire. The questionnaire method was used to collect data on the variable reading interest and the availability of learning resources, while for learning achievement the data were collected from history teachers at SMA Negeri 2 Pariaman. The analysis prerequisite test carried out included the normality test and the multicollinearity test. Hypothesis testing is done using multiple regression analysis, F test, coefficient of determination and t test. The results of this study are: (1) There is a positive effect of reading interest on the history learning achievement of students of class XII IPS in SMA Negeri 2 Pariaman. (2) There is a positive influence on the availability of learning resources on the history learning achievement of students in class XII IPS at SMA Negeri 2 Pariaman. (3) There is a positive effect of reading interest and the availability of learning resources on the history learning achievement of class XII students of SMA Negeri 2 Pariaman. Based on the research results, the results obtained 34% of the influence of reading interest and the availability of learning resources on the history learning achievement of students in class XII IPS at SMA Negeri 2 Pariaman. Keywords: Reading Interest, Availability of Learning Resources, Learning Achievement Abstrak Penelitian ini berangkat dari permasalahan dalam pembelajaran sejarah, terutama mayoritas siswa kelas XII IPS SMA Negeri 2 Pariaman nilai mid berada dibawah KKM (75). Kemudian observasi dikategorikan pada minat baca, ketersediaan sumber belajar dan rendahnya prestasi belajar siswa. Penelitian berguna untuk menganalisis hubungan Minat Baca terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS di SMA Negeri 2 Pariaman, hubungan Ketersediaan Sumber Belajar terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS di SMA Negeri 2 Pariaman, hubungan Minat Baca dan Ketersediaan Sumber Belajar terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS di SMA N 2 Pariaman. Jenis penelitian ini adalah penelitian kuantitatif dengan menggunakan program SPSS versi 16. Populasi penelitian ini adalah siswa kelas XII IPS di SMA Negeri 2 Pariaman tahun pelajaran 2020/2021 yang terdiri dari 171 siswa, sampel penelitian ini berjumlah 120 siswa yang dipilih secara acak. Uji kelayakan media dilakukan oleh validator yang mahir di bidangnya, yakni ahli materi pembelajaran sejarah. Data dikumpulkan dengan menggunakan angket. Metode angket digunakan untuk mengumpulkan data variable Minat Baca dan Ketersediaan Sumber belajar, sedangkan untuk Prestasi Belajar data dikumpulkan dari guru pelajaran sejarah di SMA Negeri 2 Pariaman. Uji prasyarat analisis yang dilakukan meliputi uji normalitas dan uji multikolinearitas. Uji hipotesis yang dilakukan menggunakan analisis regresi berganda, uji F, koefisien determinasi dan uji t. Hasil penelitian ini adalah: (1) Terdapat pengaruh positif Minat Baca terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS SMA Negeri 2 Pariaman. (2) Terdapat pengaruh positif Ketersediaan Sumber Belajar terhadap Prestasi Belajar Sejarah Siswa Kelas XII IPS SMA Negeri 2 Pariaman. (3) Terdapat pengaruh Positif Minat Baca dan Ketersediaan Sumber Belajar terhadap Prestasi Belajar Sejarah Siswa Kelas XII SMA Negeri 2 Pariaman. Berdasarkan hasil penelitian, diperoleh hasil 34% pengaruh minat baca dan ketersediaan sumber belajar terhadap prestasi belajar sejarah siswa kelas XII IPS di SMA Negeri 2 Pariaman. Kata Kunci: Minat Baca,Ketersediaan Sumber Belajar, Prestasi Belajar